A PROPOSAL OF DATA QUALITY FOR DATA WAREHOUSES ENVIRONMENT - Santoso, Leo Willyanto; Gunadi, Kartika (Institute of Research and Community Outreach - Petra Christian University, 2006)
The quality of the data provided is critical to the success of data warehousing initiatives. There is strong evidence that many organisations have significant data quality problems, and that these have substantial social and economic impacts. This paper describes a study which explores modeling of the dynamic parts of the data warehouse. This metamodel enables data warehouse management, design and evolution based on a high level conceptual perspective, which can be linked to the actual structural and physical aspects of the data warehouse architecture. Moreover, this metamodel is capable of modeling complex activities, their interrelationships, the relationship of activities with data sources and execution details.